Oxygen Deprivation and the Cellular Response to Hypoxia in Adipocytes – Perspectives on White and Brown Adipose Tissues in Obesity - Trayhurn, Paul; Alomar, Suliman Yousef (Frontiers in Endocrinology, 2015)
Relative hypoxia has been shown to develop in white adipose tissue depots of different types of obese mouse (genetic, dietary), and this leads to substantial changes in white adipocyte function. These changes include increased production of inflammation-related adipokines (such as IL-6, leptin, Angptl4 and VEGF), an increase in glucose utilisation and lactate production, and the induction of fibrosis and insulin resistance. Whether hypoxia also occurs in brown adipose tissue depots in obesity has been little considered. However, a recent study has reported low pO2 in brown fat of obese mice, this involving mitochondrial loss and dysfunction. We suggest that obesity-linked hypoxia may lead to similar alterations in brown adipocytes as in white fat cells - particularly changes in adipokine production, increased glucose uptake and lactate release, and insulin resistance. This would be expected to compromise thermogenic activity and the role of brown fat in glucose homeostasis and triglyceride clearance, underpinning the development of the metabolic syndrome. Hypoxia-induced augmentation of lactate production may also stimulate the ‘browning’ of white fat depots through recruitment of UCP1 and the development of brite adipocytes.